A hydrophilic interaction liquid chromatography–tandem mass spectrometry method for the identification and determination of cationic starch derivatives in air samples. Issue 10 (21st February 2017) - Gosetti, Fabio; Mazzucco, Eleonora; Secco, Andrea; Robotti, Elisa; Manfredi, Marcello; Marengo, Emilio
Abstract : Air monitoring of potential carcinogenic starch derivatives by a new high-throughput HILIC-MS/MS method to protect the health of workers. Abstract : The industrial processes of starch cationization are widely used and the workers must protect their health from the potential presence of toxic species, such as 2, 3-epoxypropyltrimethylammonium chloride (ETA or Quab 151®) or 3-chloro-2-hydroxypropyltrimethylammonium chloride (CTA or Quab 188®) used during the industrial processes. In this study, a sensitive and fast chromatographic method for the identification and determination of these toxic species in samples placed in fixed air sampling positions near to the reactor of starch processing has been developed and fully validated. The method is based on hydrophilic interaction liquid chromatography coupled to tandem mass spectrometry detection. The limits of detection are 3.0 ng mL −1 and 1.0 ng mL −1 for ETA and CTA, respectively, and the RSD% of the intraday ( n = 5) and the interday ( n = 35) precision of concentration determination are lower than 3.4% and 6.1%, respectively. The solid–liquid extraction procedure employed here is very simple (sonication) and fast (5 min) and allows obtaining reliable recovery values greater than 91.0%. No evidence of statistically significant matrix effects (at a 95% of confidence level) during the mass spectrometry analysis has been found. The method has been successfully applied to filter samples used in routine controls for the safety of workers involved in these type of industrial processes.